Regional Price Convergence in Australia and New Zealand, 1984-1996 - Andrew Coleman; Toby Daglish (New Zealand Government, The Treasury, 1998)
This paper uses disaggregated price data to analyse the extent and the speed of retail price convergence between New Zealand and Australia since 1984. The paper addresses several issues concerning the integration of markets in the two countries. It compares the behaviour of the prices of a set of goods in different cities in Australia with the behaviour of the prices of the same goods in New Zealand. The data is used to answer two sets of questions: first, whether there are systematic differences in the extent to which the retail goods markets between New Zealand and Australia are integrated when compared to the integration of markets between different cities within Australia; and second, whether the theory of purchasing power parity can usefully describe the effect of changes in the bilateral exchange rate on New Zealand prices.
Keywords: 330